Enhancing Our Care for the Urban Air We Breathe - Muthama, Nzoika (University of Nairobi, 2021)
Living in a city or a metropolitan area is a great promotion for human well-being, given its convenient mode of life and efficient way of working. This is so for Kenyan cities, Nairobi included. However, concerns are emerging from residents and scientists that the unprecedented development of cities has caused a range of environmental problems and exerts huge pressure on natural ecosystems that we rely on (UNEP, 2016; Asian Coalition for Housing Rights 2004; Muthama, 2019a). Several parts of Kenyan cities continue to experience overwhelming solid waste challenges and air pollution impacts among other environmental concerns. The 2017 Kenya Economic Survey estimated that 19.9 million Kenyans, representing 38.3% of the population, suffered from respiratory ailments that are exacerbated by poor air quality. The 2019 Kenya Economic Survey estimated that 21.8 million Kenyan, representing 39.3% of Kenyans, suffered from the respiratory ailment, indicating a 1% increase of the ailments at the national level. This is a pointer that the air pollution problem may be increasing.
Keywords: Kenya; Urban Environment